You've got to be in it to win it: the importance of including female athletes in screening ECG cohorts. (25th November 2020) - Janssens, K; Paratz, E; Brosnan, M; Lindqvist, A; Mitchell, A; Afridi, A; Orchard, J; Prior, D; La Gerche, A
Abstract: Background: ECG screening is widely employed in athletic populations with the aim of identifying cardiac conditions associated with sudden death. Recommendations for athlete ECG interpretation are disproportionately reliant on data from male athletes and sex-specific differences have not been adequately elucidated. Purpose: The aim of this study is to identify any different patterns in female athletic training response on ECG screening. Methods: 444 elite athletes (156 male rowers, 135 female rowers, 117 male cricketers, 36 female cricketers) underwent electrocardiogram (ECG) screening. Standard definitions were used to characterize abnormalities identified on ECG. Comparisons were made according to sex and endurance (rowing) vs skill-based (cricket) athletes (EA and SBA respectively). Results: "Potentially pathological" T-wave inversion extending to V3 was more prevalent in female athletes (9.9% vs. 2.9%, P=0.002), especially amongst endurance athletes (11.9% female EA vs. 2.8% female SBA, P=0.004) (Figure 1). As compared with males, the QTc interval was longer in female athletes (418 vs. 402ms), the QRS duration was shorter (90 vs. 100 ms) and left ventricular hypertrophy on voltage criteria were less prevalent (9.9% vs. 33.3%, P<0.001 for all). First-degree heart block and incomplete right bundle branch block were more prevalent amongst male athletes. Conclusion: Female athletes exhibit different training-related cardiac remodelling responses to exercise compared to males. A greater proportion of ostensibly healthy female athletes, especially female endurance athletes, have ECG changes that would be deemed "potentially pathological" according to current sex-agnostic guidelines. Funding Acknowledgement: Type of funding source: None